The Relationship between Identity Crises and Crises of Control - Painter-Morland, Mollie (Journal of business ethics, 2013)
Corporate governance is a theme that is important to Business Ethicists for various reasons. It relates to how and for whose benefit corporations are governed, to how important corporate decisions are taken, and to how organizational cultures are “managed.” In this article, it will be argued that in each of these respects, corporate governance relies on particular identity constructs that need to be questioned. In fact, it will be argued that the way in which corporate governance initiatives address the various crises of capitalism, allows us to gloss over some crucial ontological questions that could precipitate a more rigorous questioning of capitalist practices. The article will plot the limitations of the kind of thinking that we encounter within the corporate governance realm, and expose its problematic assumptions by exploring a selection of Deleuzoguattarian concepts. It will be argued that the challenges facing corporate governance relate to the relationship between identity crises and crises of control. We will argue that a better understanding of the nature of capitalism could open new avenues for ethical questioning of contemporary corporate practices, and put the various “crises” that capitalism faces in a new perspective.